Farm-to-Fork Livestock Traceability for Quality Meat Production: An Overview - k, Girish; P.S.; K., Nagappa; Saikia, T. (Journal of Meat Science, 2017)
Indian meat industry is emerging as one of the major players at the international meat market. According to the Agricultural and Processed Food Products Export Development Authority (APEDA) data for the year 2015-16, India’s export of animal products was Rs. 30,137 Crores; of which Rs. 26,685 Crores was from the export of 1.31MMT buffalo meat alone. This fact must be construed as an achievement in the backdrop of the unorganized nature of the Indian meat animal production and processing practices. Although developing countries are the major importers, exploration of markets of the developed countries could significantly enhance the magnitude of the export. In order to achieve this goal, the Indian meat sector must strive hard to focus its attention towards the traceability backed quality control system across the meat supply chain. Globally, become a benchmark for the differentiation between the organized and unorganized systems of meat production. Integration of key players of the livestock value chain under the traceability umbrella enables forward and backward linking and it is foreseen to bring about a paradigm shift in the livestock production practices of India. This article provides an overview of the livestock traceability and details its components, requirements, global scenario and latest initiatives by the government so as to aid in the implementation of traceability system in India.
Keywords: Meat quality; Traceability; Animal identificatio